Prediction of Runoff in Watersheds Located within Data-Scarce Regions - Ghanim A.A.J.; Beddu S.; Abd Manan T.S.B.; Al Yami S.H.; Irfan M.; Mursal S.N.F.; Mohd Kamal N.L.; Mohamad D.; Machmudah A.; Yavari S.; Mohtar W.H.M.W.; Ahmad A.; et al. (MDPI, 2023)
arid environment; catchment; design flood; flood routing; hydrograph; hydrological modeling; peak flow; prediction; rainfall-runoff modeling; runoff; streamflow; watershed; Jordan